Edukasi Artificial Intelligent dalam Implementasi Fitur Meta AI di Whatsapp - Achmad Sarwandianto; Lusi Ariyani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The use of AI by students is increasingly widespread and changing the way they learn and interact with course materials. This community service aims to provide socialization and education to UKM futsal students while promoting student rights, increasing student understanding of meta AI technology in education, as well as its potential positive and negative effects, and recognizing the importance of using certain meta AI technologies. Meta provides generative AI technology that drives the experience of using AI available through WhatsApp. Meta AI results will certainly be produced by AI as a form of response to users. The activity is carried out through socialization with discussion and lecture methods as well as questions and answers. The delivery material is in the form of slides that are displayed during the activity and sent to participants. This activity also includes assessing the level of participant understanding of meta AI technology.